2020
DOI: 10.1186/s40663-020-00266-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the local pivotal method and systematic sampling for national forest inventories

Abstract: Background The local pivotal method (LPM) utilizing auxiliary data in sample selection has recently been proposed as a sampling method for national forest inventories (NFIs). Its performance compared to simple random sampling (SRS) and LPM with geographical coordinates has produced promising results in simulation studies. In this simulation study we compared all these sampling methods to systematic sampling. The LPM samples were selected solely using the coordinates (LPMxy) or, in addition to that, auxiliary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The local pivotal method (LPM) is a form of balanced sampling method that produces small uncertainties with a minimum number of sample plots which, of course, is of considerable relevance for NFI programs. In the context of the Finnish NFI, Räty et al (2020) found, however, that LPM-sampling could not markedly improve estimates based on systematic sampling when considering several variables of interest as is typical in NFIs. Complementing the study by Magnussen et al (2020), Räty et al (2020) identify a variance estimator originally developed for LPM that is well-suited for systematic sampling.…”
Section: New Estimators and Methodsmentioning
confidence: 92%
“…The local pivotal method (LPM) is a form of balanced sampling method that produces small uncertainties with a minimum number of sample plots which, of course, is of considerable relevance for NFI programs. In the context of the Finnish NFI, Räty et al (2020) found, however, that LPM-sampling could not markedly improve estimates based on systematic sampling when considering several variables of interest as is typical in NFIs. Complementing the study by Magnussen et al (2020), Räty et al (2020) identify a variance estimator originally developed for LPM that is well-suited for systematic sampling.…”
Section: New Estimators and Methodsmentioning
confidence: 92%
“…Convenience sampling is a type of nonprobability sampling where participants of the targeted population are approached to collect data based on easy accessibility (Etikan, Musa, & Alkassim, 2016). After having consent from the administrations of the selected colleges' students from each class will be selected through systematic sampling (Raty, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Under HT estimation, many alternatives have been proposed which typically involve squared differences between a local mean of neighboring points and the observation. To make these estimators consistent with PS estimation, we plug in the residualê(t hi ) to alternative estimators presented for HT variance estimation, which is an approach taken in several other studies [19,20].…”
Section: Variance Estimatorsmentioning
confidence: 99%